Rancang Bangun Aplikasi Crowdfunding Untuk Kegiatan Edukasi dan Workshop Pada Pendidikan Sekolah Dasar - Muhammad Bagoes Ilhamy; Boni Oktaviana Sembiring; Arief Ridho Lubis; Eka Rahayu (Program Studi Sistem Informasi, 2023)
Workshop activities in the field of education are urgently needed to provide the latest information in the learning process, especially for elementary schools in remote areas. To carry out these activities requires large funds and also resource persons who have expertise in their fields. Therefore, it is necessary to have financial assistance or funding from several people which are commonly called crowdfunding and also volunteers who can help elementary schools. So that workshops and educational activities regarding education can be carried out to support the learning and teaching process properly. To overcome this problem, a crowdfunding application was built that can manage financial assistance from the community and volunteer teaching staff, so that they can carry out educational activities or workshops for elementary schools in remote areas that need these activities. This research uses the Lean Startup method as application development because the method is easy to implement so that the resulting application is in accordance with the needs. Where there are three stages, namely building, measuring and studying so that it makes it easier to design applications that are tailored to the existing target market. The results of this research are this mobile-based crowdfunding application that can help fundraise and also volunteer teaching staff to be able to hold educational activities and workshops for elementary schools in remote areas.Keywords: Crowdfunding, Workshop, Lean Startup, Elementary School.